Peruvian archaeology : a critical history - Tantaleán, Henry, 1974- (Left Coast Press, 2014)
"This book offers a unique, critical perspective on the history of Peruvian archaeology by a native scholar. Leading Peruvian archaeologist Henry Tantalean illuminates the cultural legacy of colonialism beginning with "founding father" Max Uhle and traces key developments to the present. These include the growth of Peruvian institutions; major figures from Tello and Valcarcel to Larco, Rowe, and Murra; war, political upheaval, and Peruvian regimes; developments in archaeological and social science theory as they impacted Andean archaeology; and modern concerns such as heritage, neoliberalism, and privatization. This post-colonial perspective on research and its sociopolitical context is an essential contribution to Andean archaeology and the growing international dialogue on the history of archaeology"--